An Unusual Histopathological Presentation of Epidermotropic Metastatic Pharyngeal Squamous Cell Carcinoma. (November 2020) - Savari, Omid; Shahabi, Ali; Bennett, Lauren; Somach, Stephen
Abstract : Abstract: Epidermotropic metastasis of head and neck squamous cell carcinoma is rare. We report a case of a 56-year-old white man with a history of oral squamous cell carcinoma who presented with multiple papules on the face, eyelid, and chest wall. The histopathologic examination of the skin lesions revealed nests of malignant cells with basaloid features and zones of cytoplasmic vacuolization predominantly within the dermis but focally involving the epidermis. Central necrosis, focal papilla formation, and lymph-vascular invasion were also seen. Two of these lesions, each read by different dermatopathologists, were initially diagnosed as sebaceous carcinoma. However, further evaluation, including adipophilin immunohistochemistry, confirmed the metastatic nature of the skin lesions. Cytoplasmic vacuolization in metastatic deposits of squamous cell carcinoma may mimic primary sebaceous carcinoma. This presentation highlights the need to consider the possibility of a metastatic deposit when making a diagnosis of primary sebaceous carcinoma.